A DEIXIS ANALYSIS IN JOKO WIDODO’S STATEMENT ON INDONESIA’S G20 PRESIDENCY - Miftakhul Rizqi; Yulianto Sabat (Journal of English Language and Culture, 2022)
Deixis is an important element in pragmatic studies to avoid misunderstandings between speakers and listeners. People will be misunderstanding a conversation when they don't understand the context. The purpose of this research was to determine the type of deixis contained in Joko Widodo's statement in the Indonesia’s G20 presidency and to determine the dominant type of deixis in Joko Widodo's statement. Yule's (1996) theory of deixis is used to justify the data or findings in this study. This research was designed using qualitative methods. Data was taken from the English version of the script from President Joko Widodo's statement. Following data collection, researchers found and selected data that showed that most phrases or words contain deixis types. The researchers reached conclusions after thoroughly identifying and evaluating many types of deixis detected in statements. From the data analysis, three types of deixis were found in Joko Widodo's statement in the Indonesia’s G20 presidency, namely person deixis, spatial deixis, and temporal deixis. The total deixis contained are 35 data. Persona Deiksis is the deixis that most often appears in Joko Widodo's statement in the Indonesia’s G20 presidency with a total of 26 data. In addition, spatial deixis found 2 data and temporal deixis found 7 data. Based on previous research, the researchers concluded that person deixis always dominates every moment when Joko Widodo delivers his statement.